A Rare Cause of Sciatica; Primary Pelvic Hydatid Cyst - Cetintas, Derya; Kamanli, Ayhan; Kaya Gucer, Tulun; Akgol, Gurkan; Kirkil, Cuneyt; Onur, Mehmet Ruhi (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2015)
Sciatica or sciatalgia is defined as pain radiating downward from the femur and the back of the leg. Though discal herniation and spinal stenosis are the most prevalent causes, a differential diagnosis should be carefully made from among the various etiological factors. We evaluated the case of a 37-year-old female patient with a pelvic hydatid cyst that caused sciatica. We observed complete resolution of the patient's complaints with aspiration and albendazole therapy at the 6th month of treatment. An operation was planned nearly 3.5 years later when her complaints recurred, and after the excision of the cyst, her complaints resolved. In patients with sciatica whose pain cannot be explained by intraspinal causes, the pelvic cavity should be absolutely examined; moreover, in the differential diagnosis of detected cysts, hydatid cysts, though rare, should not be forgotten.
Siyataljinin nadir bir nedeni; Primer pelvik kist hidatik
Keywords: Sciatica; pelvic cyst; hydatid cyst